PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA DIMEDIASI SELF EFFICACY PADA DOSEN POLITEKNIK ILMU PELAYARAN SEMARANG - Very Sulistiyani, Riris; Fauzan, Mohammad (Students Journal of Accounting and Banking, 2012)
The purpose of this research was to examines and analyze the influence of motivation and competence to performance of Lecturer with mediation self efficacy of the Lecturer at Merchant Marine Polytechnic Semarang. This research is taken the total population 97 respondents. The sample data is taken using a census sampling technique, the meaning is took all amount of the population is to research. In collecting data, the researcher distributes questionnaires using Likert scales which has been tried out. The validity and realibility has been fulfill base on factor analysis, alpha cronbach and also classical assumption test. The data analysis technique uses double linier analysisÂ  model test, R2 test, F- test and t-test hypotesis analysis. The result of data analysis show : Motivation influences to the self efficacy Â positively and significantly. Competence influences to the self efficacyÂ  positively buti is not significantly. Motivation, Competence and Self efficacy arenât influences to the performance of lecturer. Self efficacy did not mediate of the Motivation and Competence to the performance of lecturer.Key words Â Â Â Â Â  : motivation, competence, performance and self efficacy